When to Reduce and Fix Displaced Lesser Trochanter in Treatment of Trochanteric Fracture: A Systematic Review - Yang, Ao-Lei; Mao, Wei; Wu, Jun-Guo; He, Yi-Qun; Ni, Hao-Fei; Li, Hai-Long; Dong, You-Hai (Frontiers in Surgery, 2022)
Purpose: To systematically evaluate the benefits of reducing and fixing displaced lesser trochanter (LT) of trochanteric fractures and when this procedure is worth the effect. Methods: Four online databases (PubMed, Cochrane, Embase and Web of Science) were searched for relevant literature from database establishment till March 2021, that investigated reduction and fixation for displaced LT of trochanteric fractures. Then these papers were screened by two reviewers independently and in duplicate according to prior inclusion and exclusion criteria. Demographic data as well as data on fracture types, surgical protocols and surgical outcomes were recorded, analyzed, and interpreted. Results: Ten clinical studies with 928 patients were included, in which 48 cases had intact LT and 880 cases involved the displaced LT, of which 196 (22.27%) cases underwent reduction and fixation for LT while the rest of 684 (77.73%) cases not. In these studies, complications were evaluated as more applicable predictive parameter for operation than postoperative hip function. Conclusion: It was beneficial to reduce and fix the displaced LT when one of conditions below occurred: displacement distance of LT ≥ 2 cm; quantity of comminuted LT fragments ≥ 2 and range of LT fragments in medial wall ≥ 75%; the fracture line of LT fragments reaching or exceeding the midline of the posterior wall.